2019
DOI: 10.1097/fjc.0000000000000674
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous and Intravenous Treprostinil Pharmacokinetics in Children With Pulmonary Vascular Disease

Abstract: This study evaluated the pharmacokinetics of intravenous (IV) and subcutaneous (SC) treprostinil in pediatric patients with pulmonary vascular disease, and compared them with existing adult data from a similar cohort. Blood samples were collected from pediatric patients receiving steady-state IV or SC treprostinil and were assessed for plasma treprostinil concentration using liquid chromatography and tandem mass spectrometry. Forty participants, 15 receiving IV and 25 receiving SC treprostinil, were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…With a half‐life of 2–4 hours in human adults, subcutaneous and intravenous treprostinil infusions reach steady‐state concentrations (Css) within 10–24 hours 19,20 . The relationship between the dose and Css is linear in doses up to 125.0 ng/kg/min 21 and in a pediatric population is best described by the following equation 13 :treprostinilconcentration0.333333emngml=false(694+(65.9treprostinil dose)false)/1000…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With a half‐life of 2–4 hours in human adults, subcutaneous and intravenous treprostinil infusions reach steady‐state concentrations (Css) within 10–24 hours 19,20 . The relationship between the dose and Css is linear in doses up to 125.0 ng/kg/min 21 and in a pediatric population is best described by the following equation 13 :treprostinilconcentration0.333333emngml=false(694+(65.9treprostinil dose)false)/1000…”
Section: Discussionmentioning
confidence: 99%
“…The lower concentration of 0.99 ng/ml in patient II, may have been sampled in the midst of dose‐escalation (Figure 1) and before attaining Css after only two days of treprostinil infusion. The lower concentration may also be explained by the findings of Hall and colleagues, that within their pediatric study population, the younger the age, the lower the concentrations per dose were, implying proportional (/kg) faster metabolization and/or elimination of treprostinil in infants 13 . In an effort to negate the impact of circadian variation (20–30% difference between peaks and troughs), samples were collected at similar times during the day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, however, Hall et al found that pediatric PAH patients receiving SQ treprostinil had lower plasma concentrations compared to the IV route, although this difference was not statistically significant. Additionally, they found that children eliminate treprostinil faster, as indicated by a significantly lower concentration to dose ratio compared to adults 54 …”
Section: Prostacyclin Analoguesmentioning
confidence: 99%